Biofortified potatoes for better nutrition, East Africa. Project profile. - International Potato Center (International Potato Center, 2019)
Potatoes with high levels of iron, zinc, and vitamin C hold great promise for boosting nutrition and food security throughout East Africa. This project builds on 15 years of CIP research to introduce improved varieties of biofortified potatoes to Ethiopia and Rwanda, along with a package of support to build capacity for effective dissemination throughout the region.